Influence of the killing method of the black soldier fly on its lipid composition. (February 2019) - Caligiani, Augusta; Marseglia, Angela; Sorci, Alessia; Bonzanini, Francesca; Lolli, Veronica; Maistrello, Lara; Sforza, Stefano
Abstract: Black soldier fly (BSF, Hermetia illucens ) represents a valuable source of biomolecules and it also constitutes an economic way to valorise residual biomasses. BSF prepupae contain high amounts of lipids (37% DM basis). The present investigation aimed at studying the composition of BSF lipids and the effect of killing/storage on their quality. The main fatty acid was lauric acid, sterols were represented primarily by beta-sitosterol and campesterol. Global fatty acid and sterol profiles, determined by GC–MS, were only slightly affected by the killing procedure, while lipid classes distribution, determined by 1 H NMR, strongly changed. Prepupae killed by freezing showed a drastic reduction of acylglycerols during storage and a relevant release of free fatty acids, likely due to activation of lipases. On the contrary, prepupae killed by blanching have a stable lipid fraction constituted mainly by triacylglycerols. Therefore, killing procedure strongly influences BSF oil composition and the potential applications. Graphical abstract: Unlabelled Image Highlights: A detailed molecular characterization of black soldier fly prepupae lipids is provided. Killing method of prepupae determinates the lipid composition. Prepupae killed by freezing have an unstable lipid fraction with high acidity. Prepupae killed by blanching have a stable lipid fraction suitable for food uses.